Effects of Nitrogen and Phosphorus Addition on Soil Extracellular Enzyme Activity and Stoichiometry in Chinese Fir (Cunninghamia lanceolata) Forests - Liu, Meihua; Gan, Bingping; Li, Quan; Xiao, Wenfa; Song, Xinzhang (Frontiers in Plant Science, 2022)
Soil extracellular enzymes play an important role in microbial functions and soil nutrient cycling in the context of increasing N deposition globally. This is particularly important for Chinese fir (Cunninghamia lanceolata) forests because of the decline in soil fertility induced by successive rotation. In this study, we aimed to determine the effects of simulated N deposition (N30: 30 kg·ha-2·yr-1; N60: 60 kg·ha-2·yr-1) and phosphorus addition (P20: 20 mg·kg-1; P40: 40 mg·kg-1) on the activity and stoichiometry of soil extracellular enzymes related to soil C, N, and P cycling in Chinese fir. The results showed that N addition alone increased the activity of soil β-1,4 glucosidase (BG) but decreased the activity of N-acetyl-β-D-glucosidase (NAG) and leucine aminopeptidase (LAP). N addition increased the ratios of soil enzymes, C:N and C:P, alleviated microbial N-limitation, and aggravated microbial C-limitation. P addition alone increased enzyme activity, and P40 addition increased the ratio of BG:soil microbial biomass carbon (MBC) and (NAG+LAP):MBC, thereby aggravating C restriction. N and P co-addition significantly affected soil extracellular enzyme activity and stoichiometry. For instance, BG activity and BG:MBC increased significantly under the N30+P40 treatment, which intensified C-limitation. Soil pH was the main factor influencing enzyme activity, and these variables were positively correlated. The stoichiometric relationships of enzyme reactions were coupled with soil pH, total nitrogen (TN), and available phosphorus (AP). Our results indicate that changes in soil characteristics induced by N and P inputs influence the activities of soil microorganisms and result in changes in microbial resource acquisition strategies. This study provides useful insights into the development of management strategies to improve the productivity of Chinese fir forests under scenarios of increasing N deposition.